2021
DOI: 10.1007/s13201-021-01359-8
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the requirements engineering to the evaluation of water resources systems efficiency

Abstract: In the water resources sector, the need to adopt a new way of thinking based on a systemic approach and analysis is justified by several situations: very complex constraints that accompany the development of the sector, functional interactions between various planned developments and the multitude of actors and stakeholders involved. System engineering is a general methodological approach that encompasses all the appropriate activities to design, evolve and verify a system providing an economical and efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…At the level of comprehensive efficiency of water resources, Xu et al (2019) found that the impact of environmental regulation on green water efficiency is non-linear [26], and there is spatial heterogeneity in the threshold effect of command, market, and voluntary environmental regulation on GWRE. Rouissat B et al (2021) applied the principles of systems engineering to explore and evaluate the performance of the water resources system in Bokhlara, northwestern Algeria, taking into account a variety of factors such as water mobilization, treatment, purification, and transfer [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the level of comprehensive efficiency of water resources, Xu et al (2019) found that the impact of environmental regulation on green water efficiency is non-linear [26], and there is spatial heterogeneity in the threshold effect of command, market, and voluntary environmental regulation on GWRE. Rouissat B et al (2021) applied the principles of systems engineering to explore and evaluate the performance of the water resources system in Bokhlara, northwestern Algeria, taking into account a variety of factors such as water mobilization, treatment, purification, and transfer [27].…”
Section: Literature Reviewmentioning
confidence: 99%